Impact of Alternative Medical Device Approval Processes on Costs and Health. Issue 5 (3rd September 2014) - George, Benjamin P.; Venkataraman, Vinayak; Dorsey, E. Ray; Johnston, S. Claiborne
<x xml:space="preserve">Abstract</x> Background Medical devices are often introduced prior to randomized‐trial evidence of efficacy and this slows completion of trials. Alternative regulatory approaches include restricting device use outside of trials prior to trial evidence of efficacy (like the drug approval process) or restricting out‐of‐trial use but permitting coverage within trials such as Medicare's Coverage with Study Participation (CSP). Methods We compared the financial impact to manufacturers and insurers of three regulatory alternatives: (1) limited regulation (current approach), (2) CSP, and (3) restrictive regulation (like the current drug approval process). Using data for patent foramen ovale closure devices, we modeled key parameters including recruitment time, probability of device efficacy, market adoption, and device cost/price to calculate profits to manufacturers, costs to insurers, and overall societal impact on health. Results For manufacturers, profits were greatest under CSP—driven by faster market adoption of effective devices—followed by restrictive regulation. Societal health benefit in total quality‐adjusted life years was greatest under CSP. Insurers' expenditures for ineffective devices were greatest with limited regulation. Findings were robust over a reasonable range of probabilities of trial success. Conclusions Regulation restricting out‐of‐trial device use and extending limited insurance coverage to clinical trial participants may balance manufacturer and societal interests.